The Impact of Inbound Marketing on Word of Mouth, Brand Awareness, and Purchase Intention - Kırmızıbiber, Ahmet; Yıldız, Salih (Fırat University, 2023)
This study aims to define inbound marketing and determine its impact on marketing efforts. The target audience of the research consisted of consumers who researched on the internet before purchasing any product or service. Research data were collected through an online survey. The reliability of the collected data was tested with the Cronbach Alpha Coefficient and the validity was tested with Factor Analysis. The hypotheses created were tested with the Structural Equation Model. As a result of the analysis, it was concluded that inbound marketing (visibility management, active listening, community building and live communication) had a positive effect on word of mouth, brand awareness and purchase intention. Of the hypotheses created, only "A company's live communication has a positive effect on purchase intention." hypothesis was not supported. The limited number of studies on the subject in our domestic literature, the fact that the subject is generally handled qualitatively in the foreign literature and the few quantitative studies reveal the importance of the study. When the results of the study are also considered from the point of view of the practitioners, it is thought that it will provide important contributions to the businesses in the conditions of today's digital age, in terms of guiding them and providing positive feedback.

Bu çalışma gelen pazarlamayı tanımlayarak pazarlama çabaları üzerindeki etkisini belirlemeyi amaçlamaktadır. Araştırmanın hedef kitlesini herhangi bir ürün ya da hizmet satın almadan önce internet üzerinde araştırma yapan tüketiciler oluşturmaktadır. Araştırma verileri online anket aracılığıyla toplanmıştır. Toplanan verilerin güvenilirlikleri Cronbach Alfa Katsayısı ile geçerlilikleri ise Faktör Analizi ile test edilmiştir. Oluşturulan hipotezler Yapısal Eşitlik Modeli ile test edilmiştir. Yapılan analizler neticesinde genel olarak gelen pazarlamanın (görünürlük yönetimi, aktif dinleme, topluluk oluşturma ve canlı iletişim) ağızdan ağıza pazarlama, marka bilinirliği ve satın alma niyeti üzerinde pozitif etkisinin olduğu sonucuna ulaşılmıştır. Oluşturulan hipotezlerden yalnızca "Bir firmanın canlı iletişiminin satın alma niyeti üzerinde pozitif yönde etkisi vardır." hipotezi desteklenememiştir. Yerli literatürümüzde konu ile ilgili sınırlı sayıda çalışmanın bulunması, yabancı literatürde ise konunun genelde nitel olarak ele alınmış olması ve nicel çalışmaların az sayıda olması çalışmanın literatür için önemini ortaya koymaktadır. Çalışmanın sonuçlarının ayrıca uygulayıcılar açısından bakıldığında, günümüz dijital çağın koşullarında işletmelere yol gösterip olumlu geri dönüşümler kazandırması noktasında önemli katkılar sağlayacağı düşünülmektedir.
GELEN PAZARLAMANIN AĞIZDAN AĞIZA PAZARLAMA, MARKA BİLİNİRLİĞİ VE SATIN ALMA NİYETİ ÜZERİNDEKİ ETKİSİ